Enhancing the Numeracy Skills of Grade 8 Students through Quizizz: An Interactive Learning Approach for Improved Mathematical Proficiency - Morata, Jan Angelo (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to evaluate the effectiveness of Quizizz as a digital game-based learning tool in enhancing the numeracy skills of Grade 8 students at Louella Gotladera Alcoba National High School. Quasi- experimental research designs were employed, and 30 participants underwent pretest and posttest assessments on basic operations involving integers and real-world integer word problems. In this study, using Quizizz as an interactive tool for numeracy lessons was the intervention. Improvement measures in the students' numeracy skills are done by comparing scores for the pretest and posttest assessments. Paired sample t-tests quantitative analysis showed a significant increase in the mean score: from 19.7 (SD = 5.92) for the pretest to 29.2 (SD = 6.63) for the posttest. The t-value is -18.5 with a p-value of <0.001, which means that improvement is significant, and so it rejects the null hypothesis. These findings suggest that integrating game-based platforms like Quizziz can enhance proficiency in numeracy and positively impact students’ engagement. Besides the quantitative data, it was supported by the thematic analysis conducted on structured interviews that provided qualitative data about student experiences using Quizizz. The structured interview shows real-time feedback and other competition-related features, like leaderboards, increase engagement and enjoyment. At the same time, the understanding of numerical concepts develops over time for anxious students who want more explicit feedback. Thus, this result indicates that Quizzes will be helpful in the development of numeracy skills because they will attribute an interactive nature to learning and make it more fun. This study supports the idea that digital game-based learning platforms must be integrated into the mathematical education environment to achieve better results for students’ development of numeracy skills.